Hurthle cell adenoma and papillary microcarcinoma: a rare case of thyroid collision tumor - Palo, Seetu; Deshpande, Archana H.; Gargade, Citrawati B. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Collision tumors of the thyroid gland are histologically distinct tumors coexisting within the gland. Here, we depict a case of a 36-year-old woman who presented with anterior neck swelling of one-year duration. Local examination revealed a 3×2 cm, firm, right solitary thyroid nodule. Fine needle aspiration cytology was suggestive of Hurthle cell neoplasm. Patient underwent a right hemi-thyroidectomy. Histopathological examination showed co-existence of Hurthle cell adenoma and papillary thyroid microcarcinoma. The patient was asymptomatic during six months follow up. It is important that the surgeons and pathologists are aware of these collision tumors so that optimal therapeutic interventions can be carried out.